2022
DOI: 10.1186/s12893-022-01627-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of three-level hybrid surgery for the treatment of cervical degenerative disc disease: a retrospective study of 108 patients

Abstract: Introduction According to the different numbers and locations of cervical disc arthroplasty (CDA) and anterior cervical discectomy and fusion (ACDF), three-level hybrid surgery (HS) has many constructs. The purpose of the present study was to introduce a classification system for three-level HS and compare the two types with each other and with ACDF. Methods A retrospective study was conducted involving patients with three-level cervical degenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…Xu et al 29 compared three-level HS (Prodisc-C and MC+) and ACDF through more than 5 years of follow-up, and most patients achieved cervical balance with HS and ACDF, but there was no difference in cervical sagittal alignment parameters between the two. However, in our previous research, we more accurately classi ed threesegment HS (Prestige-LP and Zero-P) as type I versus type II and showed that type II was superior in terms of cervical lordosis and range of motion 12 . The different prostheses and cages used may be the main factor in this difference.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Xu et al 29 compared three-level HS (Prodisc-C and MC+) and ACDF through more than 5 years of follow-up, and most patients achieved cervical balance with HS and ACDF, but there was no difference in cervical sagittal alignment parameters between the two. However, in our previous research, we more accurately classi ed threesegment HS (Prestige-LP and Zero-P) as type I versus type II and showed that type II was superior in terms of cervical lordosis and range of motion 12 . The different prostheses and cages used may be the main factor in this difference.…”
Section: Discussionmentioning
confidence: 79%
“…(3) lesion segment con rmed by clinical symptoms and imaging (computed tomography (CT), magnetic resonance imaging (MRI), and X-rays); and (4) surgery on three levels between C3 and C7 12 . The exclusion criteria consisted of (1) previous surgery at the cervical spine or (2) the existence of cervical stenosis, osteoporosis, tumor, and infection.…”
Section: Participants and Procedures Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 We have confirmed that compared with ACDF, three-level HS may yield a faster recovery rate and superior radiological outcomes, such as a superiority in maintaining the cervical curvature and ROM of the total cervical spine and a smaller increase in the ROM of adjacent segments. 5 However, to date, the in vivo differences among different constructs of HS concerning threelevel CDDD have not been reported. The primary aim of the present study was to compare the in vivo differences among different hybrid constructs with one-level CDA and two-level ACDF.…”
Section: Introductionmentioning
confidence: 99%